The Concept of Children's Education in Islam Based on Surah Luqman Verses 13-15: A Comparative Analysis of the Tafsir of Sayyid Qutb, M. Quraish Shihab, and Ibn Kathir - Widodo Widodo; Armin Nurhartanto; Rina Murtyaningsih (Bulletin of Islamic Research, 2025)
This study examines the concept of children's education in Islam based on Surah Luqman verses 13-15 by examining three main interpretations: Fi Zhilalil Qur'an by Sayyid Qutb, Tafsir Al-Misbah by M. Quraish Shihab, and Tafsir Ibn Katsir. This study aims to understand the values of children's education in Islam and analyze the differences and similarities in the interpretation of the three mufasir. The research gap that was addressed was the lack of a comparative approach to these interpretations in the context of children's education. This research uses a qualitative method with a library research approach. Data were obtained from 3 books of tafsir and analyzed descriptive-comparatively. The results of the study explained that there are three main aspects: monotheistic education, adab education and respect for parents, and moral and ethical education. Tawhid education is the main foundation in shaping the Islamic character of children, as explained by Sayyid Qutb, Quraish Shihab, and Ibn Kathir. In addition, respect for parents is considered part of obedience to God, which has psychological, social, and spiritual impacts. Moral education is also emphasized as an aspect that must be applied through example and good communication between parents and children. In the context of modern education, the values that Luqman taught his children are relevant to current educational methods that are based on dialogue and persuasion. The implications of this research are relevant to the SDGs, especially quality education (SDG 4) and gender equality (SDG 5). This study supports the integration of Islamic education in the modern education system and provides insight into how Islamic values can shape the character of children in formal and non-formal education